Double pylorus in the era of proton pump inhibitors - Mansur Reimão, Sílvia (2017)
Double pylorus and gastroduodenal fistula are rare conditions and can be either congenital or acquired. We report a case of a 58-year-old man with epigastric pain and dyspepsia in which the upper gastrointestinal endoscopy revealed an acquired double pylorus, probably caused by a gastric ulcer.